The Effect of Osteopathic Visceral Manipulation on Quality of Life and Postural Stability in Women with Endometriosis and Women with Pelvic Organ Prolapse: A Non-Controlled Before-After Clinical Study - Wójcik, Małgorzata; Kampioni, Małgorzata; Hudáková, Zuzana; Siatkowski, Idzi; Kędzia, Witold; Jarząbek-Bielecka, Grażyna (Journal of clinical medicine, 2025)
Background: Visceral manipulation is a soft tissue manual work technique that originates from and is classified within the Osteopathic Manipulative Technique (OMT), focusing on the fascial tissue mobilisation of the visceral system. Manual therapy on internal organs is based on anatomy, physiology and physics. Methods: Sixty women with endometriosis and pelvic organ prolapse, aged 41.5 ± 12.02, participated in the study. The women had manipulation therapy once a week for 5 weeks. The World Health Organisation Quality of Life BREF questionnaire and a postural stability assessment were administered before and after performing visceral manipulation. Results: The p-value = 0.0093 obtained in the group with prolapses and the p-value = 0.0001 in the group with endometriosis indicated that the applied visceral manipulation improved the women's quality of life. No effect of therapy was observed on postural stability. Conclusions: Visceral manipulation improved the quality of life of both study groups of women. A significant difference was also observed when comparing the two groups for area.